Adherence policy, education and practice - an international perspective - Schneider MP; Aslani P (Centro de Investigaciones y Publicaciones Farmaceuticas, 2010)
Nonadherence to chronic therapy has become a large burden on the healthcare system of many countries. Community pharmacists are well positioned to address nonadherence as part of their overall patient care activities, and contribute to patients' quality use of medicines. Between 2008 and 2010, a series of narrative, peer-reviewed articles were published in Pharmacy Practice which focused on community pharmacists' activities in medication adherence, specifically in the areas of the education they receive, their practice, the research conducted and national or local policies. This editorial aims to summarise the key findings presented in the series, and highlight the pertinent issues and gaps in the literature. There is a need to implement global and long-term objectives focussing on enhancing the quality of education and competencies of community pharmacists and the research conducted in medication adherence, to develop guidelines for pharmacists and enhance the uptake of adherence promoting services in routine care.